Investigation of Herd Structure and Breeding Practices in Sheep Farms in Elazig Province - Koseman, Abdurrahman; Seker, Ibrahim; Kul, Selim; Karaca, Mehmet (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2022)
The aim of this research was to determine the status of sheep existence, herd structure, and basic breeding activities in farms in Elazig province. In the research, a face-to-face survey was conducted with breeders in 167 sheep farms between May-December 2020. In the study, it was determined that 61.7% of the farms had7-17 rams, 83.9% of breeders used female yearling lamb for first breeding when they were 12-17 months old, 100% used male yearling lamb for the first insemination when they were 1.5-2 years old, 71.7% of the breeders from their own farms, 83.7% of the rams kept the herd during estrus, 73.1% used salt and mineral addition for food, 77.7% of women and men milking together, 78.2% of them evaluated milk positive and sufficient as long as it wasusable for cheese-making. In addition, only 66.1% of the farms kept records, 90.4% preferred the free-breeding method, 89.9% applied natural rearing to the lambs, 55.7% of the breeders gave only straw to their sheep as roughage, 44.6% of them supplemented feeding. The existing problems and inadequacies were determined as the fact that 78.4% of them procure the feed from the factories, 97.6% of them perform the milking by hand and 89.3% of them do the shearing with shears. As a result, it has been concluded that income and economic gain can be increased by eliminating the identified deficiencies and negativities, as well as maintaining adequate-positive breeding activities in the province of Elazig, which has an important potential in terms of sheep number and breeding opportunities..
Keywords: Feeding; Farm; Sheep; Yield; Breeding